Utilization of Common and Lesser-Known Vegetables for Human Diet among Women in Oyo West Local Government Area of Oyo State - Adebimpe, Adefunke Taiwo; Oyewo, Stella Oyenike; Lhameed, Adijat Wuraola; Olunusi, Patience Abosede (Journal of Applied Food and Nutrition, 2025)
Background: Green leafy vegetables are of great nutritional value and constitute greatly to human diet. However, studies showed that some vegetables are lesser-known despite their nutritional value.Research Methods: This study was designed to determine the level of consumption of lesser known and common vegetables among women of child bearing age in Oyo west LGA, Oyo state. The research adopted descriptive design of the survey type and was guided by three research objectives. The population comprises of mothers in Oyo west Local Government Area of Oyo state. One hundred and fifty (150) women were selected using simple random sampling technique from targeted population. The instrument used for the data collection was structured questionnaire. Data were analyzed using simple percentage.Research Result: The findings showed that the following lesser-known vegetables Lactuca capensis (yanrin), solonum amenicainum (odu) cassava leaf (manihot esculenta) were not frequently consumed despite their nutritional value.Conclusion: The reasons for non-consumption of these lesser-known were given largely based on negative views expressed by residents of their communities towards these vegetables. And nutritional contents of lesser-known vegetables should be given as health talks in out-patient clinics in hospitals in view of encouraging patients to consider them and as publicity for these vital vegetables was primarily recommended.